Secondary battery
The secondary battery design with a nickel-plated stainless steel lid member and optimized opening area addresses reliability issues by enhancing peel and welding strength, improving gas discharge, and maintaining electrical conductivity, thereby increasing safety and performance.
Patent Information
- Application Number
- JP2022557276
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-15
- Filing Date
- 2021-09-10
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2041-09-10
AI Technical Summary
Secondary batteries with high energy density face challenges in maintaining reliability due to issues such as electrolyte leakage and gas discharge during extreme conditions, which can lead to combustion.
A secondary battery design featuring a lid member made of stainless steel with a nickel plating layer containing 80% or more columnar crystals, which enhances peel strength and welding strength, along with an optimized opening area for efficient gas discharge and improved electrical conductivity.
The design increases the reliability of the secondary battery by reducing electrolyte leakage and enhancing gas discharge efficiency, while maintaining high electrical conductivity and bonding strength, thus improving safety and performance under stress conditions.
Smart Images

Figure 0007613476000003 
Figure 0007613476000004 
Figure 0007613476000005
Abstract
Description
[Technical field]
[0001] The present technology relates to a secondary battery. [Background technology]
[0002] In recent years, with the widespread use of various electronic devices such as mobile phones, secondary batteries have been developed as small, lightweight, and high-energy density power sources. Since each component of a secondary battery affects the battery characteristics, various studies have been conducted (for example, see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2012 / 153728 [Patent Document 2] JP 2016-39034 A Summary of the Invention
[0004] Since such secondary batteries have a high energy density and are used for a long period of time, it is desirable for them to have high reliability.
[0005] It is therefore desirable to provide a secondary battery with improved reliability.
[0006] A secondary battery according to one embodiment of the present technology comprises a battery can having a vessel-like structure that houses a battery element therein, and a lid member that is attached to the opening surface of the battery can via a gasket, the lid member being made of nickel-plated stainless steel, and the nickel plating having a crystal structure in which the proportion of columnar crystals is 80% or more.
[0007] According to a secondary battery according to an embodiment of the present technology, the cover member attached to the battery can housing the battery element therein is made of stainless steel plated with nickel containing 80% or more columnar crystals. This allows the secondary battery to increase the peel strength of the nickel plating on the cover member and to increase the bonding strength of the welding to the cover member. Therefore, the secondary battery can increase the bonding strength of the wiring connection to the cover member, thereby making it possible to increase reliability.
[0008] Note that the effects of the present technology are not necessarily limited to the effects described here, but may be any of a series of effects related to the present technology described below. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view illustrating a configuration of a lithium ion secondary battery (cylindrical type) according to an embodiment of the present technology. [Diagram 2] 2 is an enlarged cross-sectional view showing the configuration of a main part of the lithium-ion secondary battery shown in FIG. [Diagram 3] 2 is an enlarged cross-sectional view of the lid member and its vicinity of the lithium ion secondary battery shown in FIG. 1. [Figure 4] FIG. 4 is a top view showing the planar configuration of the lid member. [Diagram 5] 4 is a schematic cross-sectional view showing a crystal structure of a plating layer of the lid member. FIG. [Figure 6] 1 is a block diagram showing a configuration of a battery pack which is an example of an application of a secondary battery; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present technology will be described in detail with reference to the drawings. The description will be given in the following order. 1. Secondary battery 1-1. Overall structure 1-2.Detailed configuration 1-3.Operation 1-4. Manufacturing method 1-5. Actions and Effects 2. Variations 3. Uses of secondary batteries
[0011] <1. Secondary battery> First, a secondary battery according to an embodiment of the present technology will be described.
[0012] The secondary battery described here is a secondary battery that obtains battery capacity by utilizing the absorption and release of an electrode reactant, and includes a positive electrode, a negative electrode, and an electrolyte. In the secondary battery, the charge capacity of the negative electrode is larger than the discharge capacity of the positive electrode in order to prevent the electrode reactant from being deposited on the surface of the negative electrode during charging. That is, the electrochemical capacity per unit area of the negative electrode is larger than the electrochemical capacity per unit area of the positive electrode.
[0013] The electrode reactant is, but is not limited to, a light metal such as an alkali metal or an alkaline earth metal. The alkali metal is lithium, sodium, potassium, etc. The alkaline earth metal is beryllium, magnesium, calcium, etc.
[0014] In the following, an example will be given in which the electrode reactant is lithium. A secondary battery that obtains battery capacity by utilizing the absorption and release of lithium is a so-called lithium ion secondary battery. In a lithium ion secondary battery, lithium is absorbed and released in an ionic state.
[0015] <1-1. Overall composition> Fig. 1 is a cross-sectional view showing the cross-sectional configuration of a secondary battery. Fig. 2 is an enlarged cross-sectional view showing the cross-sectional configuration of a main part (wound electrode body 20) of the secondary battery shown in Fig. 1. However, Fig. 2 shows only a part of the wound electrode body 20.
[0016] The secondary battery shown in FIG. 1 is a cylindrical lithium ion secondary battery in which a wound electrode body 20, which is a battery element, is housed inside a cylindrical battery can 11.
[0017] Specifically, the secondary battery includes a pair of insulating plates 12, 13 and a wound electrode body 20 inside a battery can 11. The wound electrode body 20 is an electrode body formed by winding a positive electrode 21 and a negative electrode 22 that are stacked on each other with a separator 23 interposed therebetween. The wound electrode body 20 is impregnated with an electrolytic solution that is a liquid electrolyte.
[0018] Battery can 11 contains one or more of iron (Fe), aluminum (Al), and alloys thereof, and has a hollow structure with one end closed and the other end open. The surface of battery can 11 may be plated with nickel (Ni), etc. Each of insulating plates 12, 13 extends in a direction intersecting the winding circumferential surface of wound electrode body 20, and is disposed opposite to each other with wound electrode body 20 sandwiched therebetween.
[0019] A lid member 14, a safety valve mechanism 15, and a thermosensitive resistor (PTC element) 16 are crimped to the open end of the battery can 11 via a gasket 17. This seals the open end of the battery can 11. The gasket 17 includes an insulating material. The surface of the gasket 17 may be coated with asphalt or the like.
[0020] The cover member 14 is made of stainless steel with a nickel (Ni) plated surface. The configuration of the cover member 14 will be described in detail later.
[0021] The safety valve mechanism 15 and the thermosensitive resistor element 16 are provided inside the lid member 14. The safety valve mechanism 15 is electrically connected to the lid member 14 via the thermosensitive resistor element 16. When the internal pressure of the battery can 11 reaches a certain level or higher due to an internal short circuit, external heating, or the like, the safety valve mechanism 15 reverses the disk plate 15A to cut off the electrical connection between the lid member 14 and the wound electrode body 20. The thermosensitive resistor element 16 is an element whose resistance increases with an increase in temperature. The thermosensitive resistor element 16 is provided to prevent abnormal heat generation caused by a large current.
[0022] A center pin 24 is inserted into a space provided at the center of the winding of the wound electrode body 20. However, the center pin 24 may not be provided in some cases. A positive electrode lead 25 including one or more types of conductive materials such as aluminum is connected to the positive electrode 21. The positive electrode lead 25 is electrically connected to the lid member 14 via a safety valve mechanism 15. On the other hand, a negative electrode lead 26 including one or more types of conductive materials such as nickel is connected to the negative electrode 22. The negative electrode lead 26 is electrically connected to the battery can 11.
[0023] [Positive electrode] 2, the positive electrode 21 includes a positive electrode current collector 21A and two positive electrode active material layers 21B provided on both sides of the positive electrode current collector 21A. However, the positive electrode active material layer 21B may be provided on only one side of the positive electrode current collector 21A.
[0024] The positive electrode current collector 21A includes one or more conductive materials such as aluminum, nickel, stainless steel, etc. The positive electrode current collector 21A may have a single-layer structure or a multi-layer structure.
[0025] The positive electrode active material layer 21B includes one or more positive electrode active materials capable of absorbing and releasing lithium. The positive electrode active material may be a lithium-containing compound such as a lithium-containing composite oxide or a lithium-containing phosphate compound. The lithium-containing composite oxide is an oxide containing lithium and one or more other elements as constituent elements, and has a crystal structure such as a layered rock salt type or a spinel type. The lithium-containing phosphate compound is a phosphate compound containing lithium and one or more other elements as constituent elements, and has a crystal structure such as an olivine type. The other element is one or more of any elements other than lithium. The other element is preferably an element belonging to Groups 2 to 15 of the long periodic table, and more preferably one or more of nickel (Ni), cobalt (Co), manganese (Mn), or iron (Fe). By using a lithium-containing compound containing these other elements as a positive electrode active material, the battery element can generate a higher voltage.
[0026] In addition, the positive electrode active material may be an oxide such as titanium oxide, vanadium oxide, or manganese dioxide, a disulfide such as titanium disulfide or molybdenum sulfide, a chalcogenide such as niobium selenide, or a conductive polymer such as sulfur, polyaniline, or polythiophene.
[0027] The positive electrode active material layer 21B may further include one or more of a binder or a conductive material. The binder may be a synthetic rubber such as a styrene butadiene rubber, a fluorine-based rubber, or an ethylene propylene diene synthetic rubber, or may be one or more of a polymer compound such as polyvinylidene fluoride or a polyimide. The conductive material may include one or more of a carbon material such as graphite, carbon black, acetylene black, or ketjen black, or may include a metal material or a conductive polymer.
[0028] [Negative electrode] The negative electrode 22 includes a negative electrode current collector 22A and a negative electrode active material layer 22B provided on either or both sides of the negative electrode current collector 22A.
[0029] The negative electrode current collector 22A includes one or more conductive materials such as copper, aluminum, nickel, stainless steel, etc. The negative electrode current collector 22A may have a single-layer structure or a multi-layer structure.
[0030] The surface of the negative electrode current collector 22A may be roughened by electrolysis, etc. In this case, the negative electrode current collector 22A can improve the adhesion to the negative electrode active material layer 22B by utilizing the so-called anchor effect.
[0031] In addition, the capacity of the chargeable negative electrode active material is preferably larger than the discharge capacity of the positive electrode 21 in order to prevent unintentional deposition of lithium metal on the surface of the negative electrode 22 during charging. That is, the electrochemical equivalent of the negative electrode active material is preferably larger than the electrochemical equivalent of the positive electrode 21.
[0032] The negative electrode active material layer 22B contains one or more negative electrode active materials capable of absorbing and releasing lithium. The negative electrode active material may be a carbon material, a metal-based material, or a mixture of a carbon material and a metal-based material.
[0033] The carbon material is a material containing carbon as a constituent element, and is graphitizable carbon, non-graphitizable carbon, graphite, or the like. Specifically, the carbon material is pyrolytic carbon, coke, glassy carbon fiber, organic polymer compound baked body, activated carbon, carbon black, low crystalline carbon, amorphous carbon, or the like. The shape of the carbon material is fibrous, spherical, granular, or scaly. Since the carbon material hardly changes its crystal structure when absorbing and releasing lithium, it is possible to stably obtain a high energy density. In addition, the carbon material also functions as a negative electrode conductive agent, and therefore can improve the conductivity of the negative electrode active material layer 22B.
[0034] A metallic material is a material containing one or more of metallic elements or semi-metallic elements as constituent elements. A metallic material may be a simple substance, an alloy, or a compound, or may be a mixture of two or more of these. In addition to a material consisting of two or more metallic elements, a metallic material may also include a material consisting of one or more metallic elements and one or more semi-metallic elements. Furthermore, a metallic material may contain one or more non-metallic elements as constituent elements. The structure of a metallic material may be a solid solution, a eutectic (eutectic mixture), an intermetallic compound, or a mixture of two or more of these.
[0035] The metal element or metalloid element contained in the metal-based material is an element capable of forming an alloy with lithium. The metal element or metalloid element contained in the metal-based material is magnesium (Mg), boron (B), aluminum (Al), gallium (Ga), indium (In), silicon (Si), germanium (Ge), tin (Sn), lead (Pb), bismuth (Bi), cadmium (Cd), silver (Ag), zinc (Zn), hafnium (Hf), zirconium (Zr), yttrium (Y), palladium (Pd), platinum (Pt), or the like.
[0036] The metal-based material is preferably silicon or tin, and more preferably silicon. Silicon and tin have excellent lithium absorption and release capabilities, so that the negative electrode 22 can obtain a significantly high energy density. Specifically, the metal-based material may be silicon alone, a silicon alloy, a silicon compound, tin alone, a tin alloy, a tin compound, a mixture of two or more of them, or a material containing one or more of them.
[0037] For the reasons described below, it is preferable that the negative electrode active material contains both a carbon material and a metal-based material. Specifically, a metal-based material, particularly a material containing silicon or tin as a constituent element, has a high theoretical capacity but is prone to drastic expansion and contraction during charging and discharging. On the other hand, a carbon material has a low theoretical capacity but is unlikely to expand or contract during charging and discharging. Thus, by using a carbon material and a metal-based material in combination, the negative electrode active material can obtain a high theoretical capacity (i.e., battery capacity) while suppressing the expansion and contraction of the negative electrode active material layer 22B during charging and discharging.
[0038] The negative electrode active material layer 22B may further include one or more of a binder or a conductive material. The binder may be a synthetic rubber such as a styrene butadiene rubber, a fluorine-based rubber, or an ethylene propylene diene synthetic rubber, or may be one or more of a polymer compound such as polyvinylidene fluoride or a polyimide. The conductive material may include one or more of a carbon material such as graphite, carbon black, acetylene black, or ketjen black, or may include a metal material or a conductive polymer.
[0039] [Separator] The separator 23 is a porous film interposed between the positive electrode 21 and the negative electrode 22, which allows lithium ions to pass through while preventing a short circuit caused by contact between the positive electrode 21 and the negative electrode 22. Specifically, the separator 23 may be made of a synthetic resin such as polytetrafluoroethylene, polypropylene, or polyethylene, or may be made of ceramics or the like. The separator 23 may be a single-layer film, or a multilayer film in which two or more types of porous films are laminated.
[0040] A polymer compound layer may be further provided on one or both sides of the separator 23. The polymer compound layer can improve the adhesion of each of the positive electrode 21 and the negative electrode 22 to the separator 23, and therefore the wound electrode body 20 can be made less likely to be distorted. By making the wound electrode body 20 less likely to be distorted, the decomposition reaction of the electrolyte is suppressed, and leakage of the electrolyte impregnated in the base material layer is also suppressed, so that the secondary battery can be suppressed from increasing in resistance and swelling when repeatedly charged and discharged. The polymer compound layer may contain one or more types of polymer compounds (such as polyvinylidene fluoride) that have high physical strength and chemical stability. Furthermore, the polymer compound layer may contain one or more types of inorganic particles such as aluminum oxide or aluminum nitride in order to improve safety.
[0041] [Electrolyte] The electrolyte contains a solvent and an electrolyte salt, and is impregnated into the wound electrode body 20 in which the positive electrode 21 and the negative electrode 22 are wound.
[0042] The solvent includes one or more non-aqueous solvents such as organic solvents. The non-aqueous solvent includes one or more of carbonate esters, chain carboxylate esters, lactones, or nitrile compounds. Carbonate esters refer to both cyclic carbonate esters and chain carbonate esters. Cyclic carbonate esters include ethylene carbonate, propylene carbonate, or butylene carbonate. Chain carbonate esters include dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, or methyl propyl carbonate. Chain carboxylate esters include methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, methyl isobutyrate, methyl trimethyl acetate, or ethyl trimethyl acetate. Lactones include γ-butyrolactone or γ-valerolactone. Nitrile compounds include acetonitrile, methoxyacetonitrile, or 3-methoxypropionitrile.
[0043] In addition, the solvent may further include 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, tetrahydropyran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,4-dioxane, N,N-dimethylformamide, N-methylpyrrolidinone, N-methyloxazolidinone, N,N'-dimethylimidazolidinone, nitromethane, nitroethane, sulfolane, trimethyl phosphate, or dimethyl sulfoxide.
[0044] In particular, in order to obtain better battery capacity, cycle characteristics, and storage characteristics, it is preferable that the solvent contains one or more of carbonates such as ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0045] Specifically, it is more preferable that the solvent contains a combination of cyclic carbonates such as ethylene carbonate and propylene carbonate, which are high-viscosity (high-dielectric constant) solvents (relative dielectric constant ε≧30), and chain carbonates such as dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate, which are low-viscosity solvents (viscosity≦1 mPa s).This allows the solvent to improve the dissociation of the electrolyte salt and the mobility of ions.
[0046] Furthermore, the solvent may contain, as an additive, one or more of unsaturated cyclic carbonates, halogenated carbonates, sulfonates, acid anhydrides, dinitrile compounds, diisocyanate compounds, phosphates, etc. In this way, the solvent can improve the chemical stability of the electrolyte solution.
[0047] The electrolyte salt includes one or more salts such as lithium salt. However, the electrolyte salt may include salts other than lithium salts, such as light metal salts. The lithium salt may be lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium tetraphenylborate (LiB(C6H5)4), lithium methanesulfonate (LiCH3SO3), lithium trifluoromethanesulfonate (LiCF3SO3), lithium tetrachloroaluminate (LiAlCl4), dilithium hexafluorosilicate (Li2SiF6), lithium chloride (LiCl), or lithium bromide (LiBr).
[0048] In particular, the electrolyte salt preferably contains one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, and lithium hexafluoroarsenate, and more preferably contains lithium hexafluorophosphate. In such a case, the electrolyte salt can reduce the internal resistance, thereby further improving the battery characteristics of the secondary battery.
[0049] The content of the electrolyte salt is not particularly limited, but in order to obtain high ion conductivity, the content of the electrolyte salt is preferably 0.3 mol / kg to 3.0 mol / kg relative to the solvent.
[0050] The materials for the positive electrode, negative electrode, separator, and electrolyte are not limited to the examples given above, and other materials may also be used.
[0051] <1-2. Detailed configuration> Next, the lid member 14 included in the secondary battery according to this embodiment will be described in more detail with reference to Fig. 3 to Fig. 5. Fig. 3 is an enlarged cross-sectional view of the vicinity of the lid member 14 in Fig. 1. Fig. 4 is a top view showing the planar configuration of the lid member 14. Fig. 5 is a schematic cross-sectional view showing the crystal structure of a plating layer 141 of the lid member 14.
[0052] As shown in FIGS. 3 and 4, the lid member 14 included in the secondary battery according to this embodiment includes a base material 140 made of stainless steel and a plating layer 141 made of nickel plating.
[0053] The base material 140 is a component that constitutes the shape of the lid member 14, and is provided in a circular planar shape. The base material 140 is provided with an opening 14H so as to surround a central portion 14C in point symmetry, and the central portion 14C is provided so as to protrude toward the opposite side to the battery can 11.
[0054] The plating layer 141 covers the surface of the base material 140 and is provided on the entire surface of the base material 140, including both main surfaces and end faces. Specifically, the plating layer 141 is provided on the entire surface of the base material 140, including both main surfaces of the circular planar shape, the end faces, and the inner end faces of the openings 14H. Such a plating layer 141 can be formed by forming the openings 14H and the like in the base material 140, machining the shape of the base material 140, and then immersing the entire base material 140 in a plating solution in an electroplating tank. The composition of the plating solution is not particularly limited, but an example would be nickel sulfamate=450 g / l (=450 g / dm 3 ), boric acid=30g / l(=30g / dm 3 ), S(sulfur)=8mg / l(=8mg / dm 3 ) or less. The solubility of nickel sulfamate is greater than that of nickel sulfate, so by using nickel sulfamate, a plating solution (plating bath) containing a large amount of nickel components can be obtained.
[0055] In a secondary battery, if excessive charging / discharging reactions lead to battery combustion, gas may be generated inside the battery. In such a case, in the secondary battery, the sealing of the battery can 11 on the lid member 14 side is broken in order to exhaust the gas generated inside the battery, and the gas generated inside the battery is exhausted through the opening 14H of the lid member 14.
[0056] In recent years, with the improvement of the performance of secondary batteries, the amount of gas generated during battery combustion has increased. Therefore, by expanding the area of opening 14H of cover member 14 and forming base material 140 from higher strength stainless steel, the strength of cover member 14 can be maintained while more efficiently discharging gas inside the battery during battery combustion.
[0057] Specifically, by configuring the base material 140 of the cover member 14 from stainless steel, the secondary battery can obtain better results in a drop test (a drop test conforming to JIS C 8712), as demonstrated in the examples described below. That is, a secondary battery in which the base material 140 is configured from stainless steel can better suppress leakage of electrolyte when dropped, and can therefore further increase the pass rate in the drop test.
[0058] Moreover, the opening 14H is preferably provided with an area of 9% to 12% of the cross-sectional area of the internal space of the secondary battery formed by the battery can 11 and the lid member 14. In this case, the secondary battery can obtain better results in a combustion test (UL Standard 1642 projectile test), as demonstrated in the examples described later. That is, a secondary battery having the opening 14H with an area ratio in the above range can further increase the pass rate in the above combustion test.
[0059] Specifically, when the area ratio of the opening 14H is 9% or more relative to the cross-sectional area of the internal space of the secondary battery, the gas discharge capability from the opening 14H is favorable, which is more preferable. Also, when the area ratio of the opening 14H is 12% or less relative to the cross-sectional area of the internal space of the secondary battery, the strength of the cover member 14 can be improved to a degree that can significantly suppress leakage of electrolyte in a drop test, which is preferable.
[0060] Furthermore, in the cover member 14, the base material 140 made of stainless steel, which has a relatively high electrical resistance, is entirely covered with a plating layer 141 made of nickel plating, which has a low electrical resistance. This allows the cover member 14 to maintain a lower electrical resistance between both main surfaces via the plating layer 141 formed on the end faces. Therefore, the cover member 14 can transmit the current taken from the positive electrode 21 of the wound electrode body 20 to the outside of the secondary battery with lower resistance.
[0061] Furthermore, in the secondary battery according to this embodiment, the plating layer 141 is formed so as to have a crystal structure in which the proportion of columnar crystals is 80% or more.
[0062] The columnar crystals are a crystal structure that grows vertically in the thickness direction of the nickel plating, and are likely to occur when nickel plating is formed over a long period of time at a low current value. The plating layer 141 containing many columnar crystals has fewer grain boundaries that trap impurities, so that the peel strength of the grain boundaries is less likely to decrease due to heat and pressure during welding. Therefore, the plating layer 141 containing many columnar crystals can increase the peel strength and can increase the joint strength by welding.
[0063] On the other hand, when nickel plating is formed at a large current in a short time, the nickel plating is formed containing more fine granular crystals than columnar crystals. The plating layer 141 containing many granular crystals has many grain boundaries that trap impurities, and therefore the peel strength of the grain boundaries is likely to decrease due to the heat and pressure applied during welding. Therefore, the plating layer 141 containing many granular crystals is likely to have a low peel strength and a low joint strength due to welding.
[0064] In the secondary battery of this embodiment, by providing the plating layer 141 of the lid member 14 with a ratio of columnar crystals of 80% or more, the peel strength of the plating layer 141 can be increased and the bonding strength to the lid member 14 can be increased.
[0065] Specifically, as shown in FIG. 5, the plating layer 141 includes an underlayer 141A formed on the base material 140, and a main layer 141B formed on the underlayer 141A.
[0066] The underlayer 141A is a layer that is formed on the surface of the base material 140 made of stainless steel and mainly contains granular crystals. The underlayer 141A is formed as a thin film after removing the oxide film on the surface of the base material 140 made of stainless steel.
[0067] The main layer 141B is a layer that is formed on the underlayer 141A and mainly contains columnar crystals. The main layer 141B is a layer that occupies a large part of the plating layer 141, and is formed on the underlayer 141A to be thicker than the underlayer 141A.
[0068] The boundary between the underlayer 141A and the main layer 141B may be a thickness at which columnar crystals begin to form. That is, the underlayer 141A may represent a layer of the plating layer 141 formed only of granular crystals, and the main layer 141B may represent a layer of the plating layer 141 formed including at least a portion of columnar crystals.
[0069] In the plating layer 141, it is preferable that the underlayer 141A is provided with a thickness of 0.2 μm or more and 0.8 μm or less, and the main layer 141B is provided with a thickness of 2.1 μm or more and 4.0 μm or less. In such a case, the plating layer 141 has a good balance between the underlayer 141A mainly containing granular crystals and the main layer 141B mainly containing columnar crystals, so that the peel strength of the plating layer 141 can be increased and the bonding strength of the welding to the cover member 14 can be further increased.
[0070] Specifically, when the thickness of the underlayer 141A is less than 0.2 μm, the peel strength between the underlayer 141A and the main layer 141B is excessively low, which is not preferable. When the thickness of the underlayer 141A is more than 0.8 μm, the peel strength between the underlayer 141A and the main layer 141B is excessively high, which is not preferable because it makes it difficult to melt and weld the plating layer 141 to other members. Also, when the thickness of the main layer 141B is less than 2.1 μm, the main layer 141B is excessively soft and the peel strength is excessively low, which is not preferable. When the thickness of the main layer 141B is more than 4.0 μm, the main layer 141B is excessively hard, which is not preferable because it makes it difficult to melt and weld the plating layer 141 to other members.
[0071] Note that the columnar crystals in the crystal structure of the plating layer 141 may refer to crystals in which, when the total thickness of the plating layer 141 is t, the crystal height T in the thickness direction of the plating layer 141 is 1 / 3t or more and the crystal width W in the in-plane direction of the plating layer 141 is 1 / 10t or more, as shown in Fig. 5. Also, the granular crystals may refer to crystals that do not satisfy the above-mentioned conditions for columnar crystals.
[0072] That is, in the secondary battery according to this embodiment, plating layer 141 is provided so that the ratio of columnar crystals in the entire cross section of plating layer 141 including underlayer 141A and main layer 141B is 80% or more. As an example, in the secondary battery according to this embodiment, plating layer 141 may be provided so that the area ratio of columnar crystals in a rectangular cross section represented by the product of the entire thickness t of plating layer 141 and the in-plane width w (=3t) of plating layer 141 is 80% or more.
[0073] <1-3. Operation> The secondary battery according to this embodiment can perform charge and discharge operations as follows.
[0074] During charging of the secondary battery, lithium ions are released from the positive electrode 21 and are absorbed in the negative electrode 22 via the electrolyte. During discharging of the secondary battery, lithium ions are released from the negative electrode 22 and are absorbed in the positive electrode 21 via the electrolyte. That is, in the secondary battery, lithium ions move between the positive electrode 21 and the negative electrode 22 via the electrolyte, thereby enabling charging and discharging.
[0075] <1-4. Manufacturing method> The secondary battery according to this embodiment can be manufactured by the following procedure. Specifically, after the positive electrode 21 and the negative electrode 22 are manufactured, the lithium ion secondary battery is assembled.
[0076] [Preparation of positive electrode] First, a positive electrode active material is mixed with a positive electrode binder and a positive electrode conductive agent, etc., as necessary, to prepare a positive electrode mixture. Then, the positive electrode mixture is dispersed or dissolved in an organic solvent, etc., to prepare a paste-like positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to both sides of the positive electrode current collector 21A, and then the positive electrode mixture slurry is dried to form the positive electrode active material layer 21B. The positive electrode active material layer 21B may be compression molded using a roll press machine, etc. In such a case, the positive electrode active material layer 21B may be heated and may be compression molded repeatedly multiple times.
[0077] [Preparation of negative electrode] The negative electrode 22 can be produced by a procedure similar to that for producing the positive electrode 21 described above.
[0078] Specifically, first, the negative electrode active material is mixed with a negative electrode binder and a negative electrode conductive agent, etc., as necessary, to prepare a negative electrode mixture. Then, the negative electrode mixture is dispersed or dissolved in an organic solvent, etc., to prepare a paste-like negative electrode mixture slurry. Next, the negative electrode mixture slurry is applied to both sides of the negative electrode current collector 22A, and then the negative electrode mixture slurry is dried to form the negative electrode active material layer 22B. The negative electrode active material layer 22B may be compression molded.
[0079] [Secondary battery assembly] First, a positive electrode lead 25 is connected to the positive electrode current collector 21A by welding or the like, and a negative electrode lead 26 is similarly connected to the negative electrode current collector 22A by welding or the like. Next, the positive electrode 21 and the negative electrode 22 are stacked on top of each other via the separator 23, and then the positive electrode 21, the negative electrode 22, and the separator 23 are wound to form a wound body. Next, a center pin 24 is inserted into a space provided at the winding center of the wound body.
[0080] Next, the wound body is housed inside the battery can 11 together with the insulating plates 12, 13 so that the wound body is sandwiched between the pair of insulating plates 12, 13. At this time, the positive electrode lead 25 is connected to the safety valve mechanism 15 by welding or the like, and the negative electrode lead 26 is connected to the battery can 11 by welding or the like. Next, the electrolyte is injected into the battery can 11 to impregnate the wound body with the electrolyte. As a result, the positive electrode 21, the negative electrode 22, and the separator 23 are each impregnated with the electrolyte, and the wound electrode body 20 is formed.
[0081] Thereafter, the open end of the battery can 11 is crimped via a gasket 17, and a lid member 14, a safety valve mechanism 15, and a thermosensitive resistor element 16 are attached to the open end of the battery can 11. In this way, the wound electrode body 20 is enclosed inside the battery can 11, and the secondary battery is completed.
[0082] <1-5. Actions and Effects> In the secondary battery according to this embodiment, the lid member 14 is made of stainless steel (substrate 140) that is coated with nickel plating (plating layer 141) that contains columnar crystals at a rate of 80% or more in the crystal structure. This allows the secondary battery to have a higher peel strength of the plating layer 141 and a higher bonding strength when welded to the lid member 14. Furthermore, since the substrate 140 of the lid member 14 is made of high-strength stainless steel, the secondary battery can further suppress leakage of electrolyte when dropped. Therefore, the secondary battery according to this embodiment can improve its reliability.
[0083] In the secondary battery, the plating layer 141 is preferably provided to include an underlayer 141A having a thickness of 0.2 μm to 0.8 μm and a main layer 141B having a thickness of 2.1 μm to 4.0 μm. In this case, the peel strength of the plating layer 141 can be increased and the bonding strength of the welding to the lid member 14 can be further increased, thereby improving the reliability of the secondary battery.
[0084] In addition, in the secondary battery, the area ratio of opening 14H provided in lid member 14 is preferably 9% to 12% of the cross-sectional area of the internal space of the secondary battery formed by battery can 11 and lid member 14. In this case, the secondary battery can achieve both the ability to discharge gas from opening 14H and the strength of lid member 14, thereby further improving reliability.
[0085] Furthermore, in the secondary battery, a nickel plating layer 141 may be provided on the entire surface, including the end faces, of the base material 140. In such a case, the secondary battery can further increase the electrical conductivity between both main surfaces of the lid member 14, making it possible to extract current from the battery element with lower resistance.
[0086] <2. Modifications> Next, modified examples of the secondary battery according to the present embodiment will be described. The configuration of the secondary battery can be modified as appropriate, as described below. However, any two or more of the modified examples described below may be combined with each other.
[0087] [Variation 1] In the above embodiment, the separator 23 is described as being a porous film. However, the separator 23 may be a laminated film including a polymer compound layer.
[0088] Specifically, the separator 23 may be configured to include a substrate layer that is the above-mentioned porous film, and a polymer compound layer provided on one or both sides of the substrate layer. The polymer compound layer includes a polymer compound such as polyvinylidene fluoride, which has excellent physical strength and is electrochemically stable. This allows the separator 23 to improve adhesion to each of the positive electrode 21 and the negative electrode 22, thereby suppressing positional deviation inside the wound electrode body 20. Therefore, the secondary battery can suppress the occurrence of swelling even when a decomposition reaction of the electrolyte occurs.
[0089] One or both of the base material layer and the polymer compound layer of the separator 23 may contain a plurality of particles. The type of the plurality of particles may be any one or more types of particles such as inorganic particles and resin particles. In this way, the secondary battery can dissipate heat by the plurality of particles when heat is generated, thereby improving heat resistance and safety. The inorganic particles are not particularly limited, and may be particles such as aluminum oxide (alumina), aluminum nitride, boehmite, silicon oxide (silica), titanium oxide (titania), magnesium oxide (magnesia), and zirconium oxide (zirconia).
[0090] The separator 23 of a laminated film including a polymer compound layer can be produced by preparing a precursor solution containing a polymer compound and an organic solvent, and then applying the precursor solution to one or both sides of a base layer.
[0091] Even when such a separator 23 is used, lithium becomes movable between the positive electrode 21 and the negative electrode 22, so that the secondary battery can obtain the same effect.
[0092] [Variation 2] In the above embodiment, the element structure of the wound electrode body 20 has been described as being a laminated type in which the sheet-like positive electrode 21, negative electrode 22, and separator 23 are laminated. However, the element structure of the wound electrode body 20 is not limited to the above embodiment. Specifically, the element structure of the wound electrode body 20 may be a zigzag-folded element structure in which the positive electrode 21, negative electrode 22, and separator 23 are folded, or may be a stack-and-folded element structure.
[0093] <3. Uses of secondary batteries> The use (application example) of the secondary battery is not particularly limited. The secondary battery used as a power source may be used as a main power source for electronic devices and electric vehicles, etc., or may be used as an auxiliary power source. The main power source is a power source that is used preferentially regardless of the presence or absence of other power sources, and the auxiliary power source is a power source that is used instead of the main power source or a power source that is switched from the main power source.
[0094] Specific examples of applications of secondary batteries include electronic devices such as video cameras, digital still cameras, mobile phones, notebook computers, headphone stereos, portable radios, and portable information terminals, storage devices such as backup power sources and memory cards, power tools such as electric drills and electric saws, battery packs mounted on electronic devices, medical electronic devices such as pacemakers and hearing aids, electric vehicles such as electric cars (including hybrid cars), and power storage systems such as home or industrial battery systems that store power in preparation for emergencies, etc. In these applications, one secondary battery may be used, or multiple secondary batteries may be used.
[0095] The battery pack may be configured using a single cell or a battery pack. The electric vehicle is a vehicle that operates (runs) using a secondary battery as a driving power source, and may be a hybrid vehicle that also includes a driving source other than a secondary battery. The home power storage system is capable of operating home electrical appliances and the like by utilizing power stored in a secondary battery, which is a power storage source.
[0096] Here, an example of an application of the secondary battery will be specifically described. The configuration of the application described below is merely an example and can be appropriately changed.
[0097] Figure 6 shows the block configuration of a battery pack. The battery pack described here is a battery pack (a so-called soft pack) that uses one secondary battery, and is installed in electronic devices such as smartphones.
[0098] 6, the battery pack includes a power source 111 and a circuit board 116. The circuit board 116 is connected to the power source 111, and includes a positive terminal 125, a negative terminal 127, and a temperature detection terminal 126.
[0099] The power source 111 includes one secondary battery. In the secondary battery, a positive electrode is connected to a positive terminal 125, and a negative electrode is connected to a negative terminal 127. The power source 111 can be connected to the outside via the positive terminal 125 and the negative terminal 127, and can be charged and discharged via the positive terminal 125 and the negative terminal 127. The circuit board 116 includes a control unit 121, a switch unit 122, a PTC element 123, and a temperature detection unit 124. However, the PTC element 123 may be omitted.
[0100] The control unit 121 includes a central processing unit (CPU) and a memory, and controls the operation of the entire battery pack. The control unit 121 detects and controls the usage state of the power source 111 as necessary.
[0101] When the voltage of the power source 111 (secondary battery) reaches the overcharge detection voltage or the overdischarge detection voltage, the control unit 121 can turn off the switch unit 122 to prevent a charging current from flowing through the current path of the power source 111. The overcharge detection voltage and the overdischarge detection voltage are not particularly limited. As an example, the overcharge detection voltage is 4.2V±0.05V, and the overdischarge detection voltage is 2.4V±0.1V.
[0102] The switch unit 122 includes a charge control switch, a discharge control switch, a charge diode, a discharge diode, etc., and switches between the presence and absence of a connection between the power source 111 and an external device in response to an instruction from the control unit 121. The switch unit 122 includes a metal-oxide-semiconductor field-effect transistor (MOSFET) etc. The charge / discharge current is detected based on the ON resistance of the switch unit 122.
[0103] Temperature detection unit 124 includes a temperature detection element such as a thermistor, measures the temperature of power supply 111 using temperature detection terminal 126, and outputs the temperature measurement result to control unit 121. The temperature measurement result measured by temperature detection unit 124 is used when control unit 121 controls charging and discharging of power supply 111 in the event of abnormal heat generation, and when control unit 121 performs correction processing for the remaining capacity of power supply 111 when calculating the remaining capacity, etc. EXAMPLES
[0104] The secondary battery according to the present embodiment will be described in more detail below with reference to examples and comparative examples. Note that the examples shown below are examples for showing the feasibility and effects of the secondary battery according to the present embodiment, and the present technology is not limited to the following examples.
[0105] (Secondary battery manufacturing) Secondary batteries according to the examples and comparative examples were manufactured by the following procedures.
[0106] First, a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent were mixed to prepare a positive electrode mixture, and then the positive electrode mixture was poured into an organic solvent to prepare a paste-like positive electrode mixture slurry. The prepared positive electrode mixture slurry was applied to both sides of a positive electrode current collector (aluminum foil) and heated and dried to form a positive electrode active material layer. Then, the positive electrode active material layer was compression-molded using a roll press machine to produce a positive electrode.
[0107] Next, the negative electrode active material, the negative electrode binder, and the negative electrode conductive agent were mixed to prepare a negative electrode mixture, and the negative electrode mixture was then poured into an organic solvent to prepare a paste-like negative electrode mixture slurry. The prepared negative electrode mixture slurry was applied to both sides of a negative electrode current collector (copper foil) and heated and dried to form a negative electrode active material layer. Then, the negative electrode active material layer was compression-molded using a roll press machine to produce a negative electrode.
[0108] Next, an electrolyte salt was added to the solvent and dissolved in the solvent to prepare an electrolyte solution.
[0109] Thereafter, a positive electrode lead was connected to the positive electrode by welding or the like, and a negative electrode lead was connected to the negative electrode by welding or the like. Next, the positive electrode and the negative electrode were stacked on each other via a separator and wound to form a wound body, and the wound body was stored inside a cylindrical battery can with an outer diameter of 26 mm. At this time, the positive electrode lead was connected to a safety valve mechanism by welding or the like, and the negative electrode lead was connected to the battery can by welding or the like, and the electrolyte was injected into the inside of the battery can to impregnate the wound body with the electrolyte. Next, the open end of the battery can was sealed via a gasket with a lid member made of nickel-plated stainless steel, and the wound body was enclosed inside the battery can to produce a secondary battery.
[0110] (Test methods for secondary batteries) For each of the secondary batteries according to the examples and comparative examples manufactured above, the proportion of columnar crystals in the plating layer was measured, and a welding test, a drop test, and a combustion test were also carried out.
[0111] The proportion of columnar crystals in the plating layer was calculated by exposing a cross section of the plating layer using a Focused Ion Beam (FIB) device and then observing the exposed cross section of the plating layer with a Scanning Ion Microscope (SIM) at a magnification of 30,000 times.
[0112] Specifically, the area ratio of columnar crystals in a cross section of the plating layer having a width of 3t in the in-plane direction of the plating layer was calculated, where t is the total thickness of the plating layer. Note that columnar crystals are defined as crystals whose crystal height in the thickness direction of the plating layer is 1 / 3t or more and whose crystal width in the in-plane direction of the plating layer is 1 / 10t or more, relative to the total thickness t of the plating layer.
[0113] The welding test was carried out in the following manner, with 32 tests. Specifically, a lead made of tin-plated copper (thickness t = 0.15 mm) was resistance welded to the center of the lid member so that the weld mark was 1 mm or more in diameter. The welded lead was then peeled off from the fixed lid member with a specified force, and an evaluation was made as to whether or not holes (material fracture) occurred in the lead. In this test, if holes occurred in the lead, it was determined that the lead was well welded to the lid member, and the results were evaluated as "number of tests in which holes occurred in the lead / total number of tests." The more tests in which holes occurred in the lead, the better the welding test results.
[0114] The drop test was conducted in accordance with JIS C 8712, with 30 tests. Specifically, the secondary battery was dropped three times, lid side down, from a height of 10m onto a concrete floor, and then the presence or absence of electrolyte leakage from the secondary battery was evaluated. In this test, a battery that did not leak electrolyte after the drop was judged as "A," and a battery that leaked even a small amount of electrolyte after the drop was judged as "B." "A" is better than "B."
[0115] The flammability test was conducted in accordance with the UL Standard 1642 projectile test, with 10 tests. In this test, if 90% or more of the tests passed, it was judged as "A", and if 10% or more of the tests failed, it was judged as "B". "A" is better than "B".
[0116] (Evaluation Results) First, the electrical resistance of the lid member of the secondary battery according to the embodiment manufactured above was measured by the four-terminal method. Specifically, the electrical resistance between one main surface of the lid member facing the inside of the secondary battery (the area outside the opening) and the other main surface of the lid member facing the outside of the secondary battery (the area at the center) was measured by the four-terminal method, and the arithmetic average value of 10 samples was calculated.
[0117] As a result, the electrical resistance value of the cover member in which nickel plating was applied to the entire surface including the end faces was 1.55 mΩ, and the electrical resistance value of the cover member in which nickel plating was applied only to both main surfaces excluding the end faces was 1.74 mΩ. Therefore, it is found that in the cover member in which nickel plating is applied to the entire surface including the end faces, current flows through the plating layer covering the surface of the base material made of stainless steel, and therefore the electrical resistance value can be reduced compared to the cover member in which nickel plating is not applied continuously between both main surfaces.
[0118] Next, the evaluation results of the welding test of each of the secondary batteries according to the examples and comparative examples produced above are shown in Table 1 below.
[0119] [Table 1]
[0120] As shown in Table 1, the secondary batteries according to Examples 1 to 8 have a ratio of columnar crystals in the plating layer of 80% or more, and therefore show better results in the welding test than the secondary batteries according to Comparative Examples 1 and 2. Moreover, the secondary batteries according to Examples 1 to 5 have thicknesses of the base layer and main layer in the plating layer within the above-mentioned preferred ranges, and therefore show even better results in the welding test than the secondary batteries according to Examples 6 to 8.
[0121] Next, the evaluation results of the drop test and the combustion test for each of the secondary batteries according to the examples manufactured above are shown in the following Table 2. In the secondary batteries according to the following Examples 10 to 14, the ratio of columnar crystals in the plating layer was 80%.
[0122] [Table 2]
[0123] As shown in Table 2, the secondary batteries according to Examples 10 to 13 have a ratio of the total area of the openings to the cross-sectional area of the secondary battery of 9% or more, and therefore show better results in the drop test than Example 14. Also, the secondary batteries according to Examples 11 to 14 have a ratio of the total area of the openings to the cross-sectional area of the secondary battery of 12% or less, and therefore show better results in the combustion test than Example 10. That is, it can be seen from the results shown in Table 2 that the ratio of the total area of the openings to the cross-sectional area of the secondary battery is preferably 9% or more and 12% or less.
[0124] Although the present technology has been described above with reference to an embodiment and examples, the configuration of the technology is not limited to the configuration described in the embodiment and examples and can be modified in various ways.
[0125] Although the above description has been given with respect to the case where the electrode reactant is lithium, the electrode reactant is not particularly limited. Specifically, as described above, the electrode reactant may be other alkali metals such as sodium and potassium, or may be alkaline earth metals such as beryllium, magnesium, and calcium. In addition, the electrode reactant may be other light metals such as aluminum.
[0126] The effects described in this specification are merely examples, and the effects of the present technology are not limited to the effects described in this specification. Therefore, other effects may be obtained with respect to the present technology.
Claims
1. a battery can having a vessel-like structure for accommodating a battery element therein; a cover member attached to an opening surface of the battery can via a gasket; Equipped with The cover member is made of nickel-plated stainless steel, The nickel plating includes columnar crystals, The columnar crystals refer to crystals that have grown vertically in a thickness direction of the nickel plating, and have a crystal height in the thickness direction of the nickel plating that is greater than a crystal width in an in-plane direction of the nickel plating, and in a cross section of the nickel plating, the crystal height in the thickness direction of the nickel plating is 1 / 3 or more of the thickness of the nickel plating and the crystal width in the in-plane direction of the nickel plating is 1 / 10 or more of the thickness of the nickel plating, a width of the nickel plating in an in-plane direction is three times a thickness of the nickel plating, and an area ratio of the columnar crystals in a rectangular cross section represented by the product of the thickness of the nickel plating and the width of the nickel plating in the in-plane direction is 80% or more.
2. The nickel plating is applied to the entire surface including the end surface of the stainless steel. The secondary battery according to claim 1 .
3. The nickel plating includes a base layer having a thickness of 0.2 μm or more and 0.8 μm or less formed on the stainless steel, and a main layer having a thickness of 2.1 μm or more and 4.0 μm or less formed on the base layer. The secondary battery according to claim 1 or 2.
4. The cover member has an opening, 4. The secondary battery according to claim 1, wherein a ratio of an opening area of the opening to a cross-sectional area of an internal space formed by the battery can and the lid member is 9% to 12%.
5. The secondary battery according to claim 1 , wherein the battery can has a cylindrical shape.
6. It is a lithium-ion secondary battery. The secondary battery according to claim 1 .
Citation Information
Patent Citations
The sealed alkaline storage battery
JP1983144759U
Battery and battery module
JP2003323869A
Steel plate for battery electrode terminal, and battery including the same
JP2016039034A
Metal-resin bonded product
JP2019181710A
Ni-plated metal sheet, welded structure, and method for making battery material
WO2012153728A1